Outcome of solid and cavitary pulmonary nodules in rheumatoid arthritis patients— case series - AKSOY, AYSUN; BOZKURTLAR, EMİNE; KARAKURT, SAİT; ERYÜKSEL, SEMİHA EMEL; İNANÇ, GÜZİDE NEVSUN; KOCAKAYA, DERYA (My University, 2022)
© TÜBİTAK.Background/aim: Rheumatoid pulmonary nodule can be detected in up to 32% of rheumatoid arthritis (RA) patients and approximately one-third of nodules may cavitate. We aimed to evaluate characteristics of patients with RA developing cavitary pulmonary nodular (CPN) lesions under disease-modifying antirheumatic drugs (DMARDs), follow-up of both cavitary and solid nodules, and their outcome with the treatment. Materials and methods: RA patients who presented with CPN lesions during follow-up were recruited retrospectively in this case series analysis. Total numbers and mean diameters of cavitary and solid nodules in each thorax computed tomography (CT) have been determined and followed up by two experienced pulmonary physicians. Moreover, changes in treatment after the development of the CPN lesions and characteristics of cavitary nodules were collected. Results: Eleven patients with CPN lesions were reported. At the time of CPN diagnosis, more patients were taking leflunomide than methotrexate (81% vs 19%). Half of the patients were receiving biologic therapy and only 18% were taking anti-TNF drugs. After a median of 24 (3–65) months of follow-up, the regression of CPN lesions was determined in 45% (5/11) of patients. Four of these 5 (80%) patients were switched to a treatment regimen without leflunomide and three of them to nonanti-TNF biologic treatment or targeted synthetic DMARDs (tocilizumab, tofacitinib, and rituximab). Conclusion: CPN lesions seen in RA patients are often pulmonary manifestations of the underlying disease; however, one must rule out malignancies or infections. If lesions progress under DMARDs, it is advised to discontinue synthetic DMARDs (LEF/MTX) and switch to another biological DMARD with different modes of action.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Biologic drugs; cavitary nodule; leflunomide; rheumatoid arthritis; solid nodule